Advanced Therapy Medicinal Products' Translation in Europe: A Developers' Perspective - Pizevska, Maja; Kaeda, Jaspal; Fritsche, Enrico; Elazaly, Hisham; Reinke, Petra; Amini, Leila (Frontiers in Medicine, 2022)
Advanced Therapy Medicinal Products (ATMPs) comprising cell, gene, and tissue-engineered therapies have demonstrated enormous therapeutic benefits. However, their development is complex to be managed efficiently within currently existing regulatory frameworks. Legislation and regulation requirements for ATMPs must strike a balance between the patient safety while promoting innovations to optimize exploitation of these novel therapeutics. This paradox highlights the importance of on-going dynamic dialogue between all stakeholders and regulatory science to facilitate the development of pragmatic ATMP regulatory guidelines.